2016
DOI: 10.1155/2016/6973175
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose and Lipopolysaccharide Prime NLRP3 Inflammasome via ROS/TXNIP Pathway in Mesangial Cells

Abstract: While inflammation is considered a central component in the development in diabetic nephropathy, the mechanism remains unclear. The NLRP3 inflammasome acts as both a sensor and a regulator of the inflammatory response. The NLRP3 inflammasome responds to exogenous and endogenous danger signals, resulting in cleavage of procaspase-1 and activation of cytokines IL-1β, IL-18, and IL-33, ultimately triggering an inflammatory cascade reaction. This study observed the expression of NLRP3 inflammasome signaling stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 49 publications
3
74
0
Order By: Relevance
“…In addition to these points, stress-response pathway activation would be induced by ROS accumulation immediately, and apoptosis would be subsequently increased [32]. Simultaneously, many apoptosis stimuli, including treatment with tumour necrosis factor (TNF)-α [33] and lipopolysaccharide (LPS) [34] and growth factor withdrawal, can induce ROS generation through mitochondria [35]. In addition, antioxidants such as N-acetylcysteine, thioredoxin and MnSOD can mediate this effect and postpone apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these points, stress-response pathway activation would be induced by ROS accumulation immediately, and apoptosis would be subsequently increased [32]. Simultaneously, many apoptosis stimuli, including treatment with tumour necrosis factor (TNF)-α [33] and lipopolysaccharide (LPS) [34] and growth factor withdrawal, can induce ROS generation through mitochondria [35]. In addition, antioxidants such as N-acetylcysteine, thioredoxin and MnSOD can mediate this effect and postpone apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified that TXNIP was a direct target of miR‐335‐3p at its 3′‐UTR mRNA by bioinformatics, which was confirmed by luciferase reporter assays, and miR‐335‐3p overexpression suppressed NPC apoptosis and TXNIP expression at mRNA and protein levels, while silencing miR‐335‐3p led to an opposite effect. TXNIP, an endogenous inhibitor of thioredoxin, mediates NLRP3 inflammasome activation in various inflammatory diseases including, but not limited to diabetic retinopathy , rheumatoid arthritis (RA) , nonalcoholic fatty liver disease (NAFLD) . In this study, we confirmed that TXNIP expression at mRNA and protein levels was increased in IDD patients as compared to patients with spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is typically associated with persistent inflammation response due to infiltration of immune cells and cytokines [14]. Several inflammatory cytokines are activated during the process of wound healing.…”
Section: Discussionmentioning
confidence: 99%